Deciphering the trigger warning debate: a qualitative analysis of online comments. Issue 7 (2nd October 2020) - George, Evan; Hovey, Angela
ABSTRACT: In 2014, a US college created a policy requiring faculty to provide trigger warnings for students. This spurred a heated debate across North America regarding the need for and efficacy of trigger warnings in classes. A content analysis of comment responses (over 1500) to 20 articles on the topic of trigger warnings from two higher education news journals (Inside Higher Ed; Chronicle of Higher Education) was performed . The trends, quality, and nature of the comments were categorized and opinions were gleaned in an effort to understand common arguments for or against the implementation of trigger warnings in the classroom. Findings against trigger warnings included concerns about academic freedom, infantalization of students, and unfair responsibility for professors; whereas findings for included promotion of positive pedagogical values, recognition of human courtesy, and supporting student mental health. This study helps to inform pedagogical practices and further research on best practices in higher education.